Implementing the Principles of Transparency and Best Practice in Scholarly Publishing - Kim, Kihong (Science Editing, 2019)
The third edition of the Principles of Transparency and Best Practice in Scholarly Publishing was published in January, 2018. This edition, which consists of 16 principles related to all aspects of scholarly publishing such as journal governance, publication ethics, copyright, archiving and profit model, has been prepared by the collaboration of four organizations, which are the Committee on Publication Ethics (COPE), the Directory of Open Access Journals (DOAJ), the Open Access Scholarly Publishers Association (OASPA), and the World Association of Medical Editors (WAME) [1]. Most of these principles are self-evident and can be considered as essential ingredients in publishing scholarly journals in an ethically, academically and entrepreneurially transparent manner. Since July, 2018, Science Editing has fully adopted them in the editorial policy, which can be found in our web page about Best Practice (https://www.escienceediting.org/about/best_practice.php). This has been followed by many Korean journals since then.